LGG-04. Clinical and molecular characterization of metastatic pediatric low grade gliomas. (3rd June 2022) - Lindsay, Holly; Stuckert, Austin; Chintagumpala, Murali; Su, Jack; Baxter, Patricia; Okcu, M Fatih; Malbari, Fatema; Rednam, Surya; Reuther, Jacquelyn; Fisher, Kevin; Scollon, Sarah; Plon, Sharon; et al.
Abstract: BACKGROUND: Despite being the most common central nervous system tumor in children, ≤5% of pediatric low grade gliomas (pLGG) present with metastases. Due to their rarity, there is a paucity of clinical and molecular data in metastatic pLGGs. To address the need, we analyzed a cohort of 22 patients with pLGG followed at Texas Children's Hospital who presented with metastatic disease. RESULTS: The predominant histology was pilocytic astrocytoma (16/22, 73%); average age at diagnosis was 4 years 11 months. The most common sites of primary disease were optic pathway/chiasm (7/22, 32%) and suprasellar (5/22, 23%). Metastatic disease was most commonly noted in the leptomeninges (12/22, 55%). 16/22 patients (73%) were treated with up-front medical therapy following tumor biopsy/resection, the majority with carboplatin-based therapy; the remaining 6 patients received only surgery up-front. Only 2/22 patients (9%) did not progress after their initial treatment with an average follow-up of 42 months. 14 patients (14/22, 64%) had continued disease progression after at least 2 therapeutic interventions; however, only 3 patients (3/22, 14%) eventually received craniospinal radiation. 10 patients (10/22, 45%) received treatment with an agent targeting the mitogen-activated protein kinase (MAPK) pathway. 20/22 patients (91%) were alive at last follow-up (average 72 months). 4/21 patients (19%) harbored a BRAF V600E mutation while 7/20 (35%) had a BRAF::KIAA1549 duplication/fusion. 8/20 patients (40%) were wildtype for both analyzed molecular alterations in BRAF. 8 patients had germline whole exome sequencing performed and all were negative for pathogenic/likely-pathogenic variants related to their clinical phenotype. Methylation analyses are pending on patients with available tumor tissue. CONCLUSION: In our cohort of patients with metastatic pLGG, most tumors progressed despite numerous therapeutic regimens, but the overall survival was >90%. 40% of patients were wild type for the 2 most common MAPK alterations seen in pLGG.